Dinâmica do carbono em latossolo vermelho sob sistemas de preparo de solo e de culturas - Campos, Ben-hur Costa de (2006)
The soil C stock is a consequence of the balance between the C losses by the CO2 emission (associate to the heterotrofic microorganisms activity) and erosion, and to C inputs, associate to organic compounds input by the vegetal photosynthesis process. In order to evaluate the soil tillage and crop systems regarding to the C inputs by the residues and the C losses by the CO2 evolution and its consequences on the soil C stocks, a long term experiment (19 years) was carried out over a Rhodic Hapludox. This experiment is located in FUNDACEP, Cruz Alta, RS, Brazil. The main treatments were soil tillage systems: conventional tillage (CT) and no-tillage (NT). Subplots were tree commercial crop systems: winter wheat/soybean defined as monocropping system (R0), black oat/soybean/winter wheat/soybean defined as a winter crop rotation system (R1), and black oat/soybean/black oat+common vetch/maize/oil radish/winter wheat/soybean (R2) defined as intensive crop rotation system. The soil in NT system, averaged over crop systems, showed higher SOC and TN stocks and their particulate pools than the soil in CT on the shallow soil layer (0 - 5 cm), while the CT showed higher particulate organic carbon and nitrogen stocks (POC and PN) on the 5 - 10 cm layer. The soil in NT showed 1.6% more SOC than CT, averaged on the rotation systems, estimated by the layer equivalent method. To the mass equivalent method this difference increase to 4.5%. The crop rotation R2 associated to the NT (NT R2) showed higher mineral-associated carbon, SOC, mineral-associated N and TN stocks than the others treatments, on the 0 30 cm layer. The soil organic matter restoration was more influenced by the crop rotations systems, with high biomass input, than the tillage system adopted. This result most likely is due to differences in the biomass inputs. Once the NT, in averaged on crop systems, resulted in only 14% higher C addition than the CT. When associated to the R2 (NT R2) this difference increased to 68% compared to the CT without crop rotation (CT R0). The C-CO2 losses, evaluated by CO2 flux, were similar among treatments (soil tillage and crop systems), it is mostly influenced by the moisture and soil temperature.